2023
DOI: 10.1002/bio.4484
|View full text |Cite
|
Sign up to set email alerts
|

Fuel‐dependent, shape‐selective, distinct blue and green photoluminescence from α‐Bi2O3 and β‐Bi2O3 synthesised using microwave combustion

Abstract: In the current study, α‐Bi2O3 and β‐Bi2O3 were synthesised using a one‐step, novel, solid–solid combustion technique. The reaction rate was increased with the use of microwaves (molecular heating) compared to direct or indirect heating. A strong relationship was observed between the fuel, polymorphic structure, shape and optical properties of the synthesised Bi2O3. Photoluminescence studies reveal that two major visible emissions are observed for all samples. The two emissions are distinct with a broad peak in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
2
0
0
Order By: Relevance
“…The band gap energies for a pure single phase of B1 and B3 match well with the works by Bashir et al and Sun et al 46,48 The mixed phase B2 has a band gap energy between the single phase B1 and B3. Previous structural analysis reveals that few tetrahedra grew on the triangular sheet matrix in B2, which would result in a slightly narrowed band gap energy relative to the pure β-Bi 2 O 3 sheet matrix of B1.…”
Section: F Rsupporting
confidence: 88%
“…The band gap energies for a pure single phase of B1 and B3 match well with the works by Bashir et al and Sun et al 46,48 The mixed phase B2 has a band gap energy between the single phase B1 and B3. Previous structural analysis reveals that few tetrahedra grew on the triangular sheet matrix in B2, which would result in a slightly narrowed band gap energy relative to the pure β-Bi 2 O 3 sheet matrix of B1.…”
Section: F Rsupporting
confidence: 88%
“…Figure 3a shows that the variations in the band gap energy values of the Bi 2 O 3 microrods were in the range of 2.25-3.18 eV. These results were supported by the UV-DRS spectrum analysis, as depicted in Figure 3b, where the band gap energy values of 2.79 eV obtained for the Bi 2 O 3 microrods were consistent with the experimental findings [69][70][71]. The outcomes demonstrated that the as-prepared Bi 2 O 3 microrods with a band gap of 2.79 eV were enough to activate photocatalysis under visible light.…”
Section: Band Gap Energy Valuesupporting
confidence: 85%